Bone: A study of machining-induced damage and the role of interstitial fluid - Robles Linares Alvelais, Jose Alberto (2022)
Bone cutting is a common process in orthopaedics, dentistry and neurosurgery. However, it comprises a challenging set of tasks when it comes to machining analysis and damage assessment due to its complex hierarchical and porous microstructure. Additionally, given its biological nature, bone is not only an engineering material, but also a tissue that holds living cells and interstitial fluid within.